(3bUjOI aj eOM GdfHj Udi Gddg Ydjg hSdes - (3eMeO Hf YHO Gddg Hf MSf GdTGWHjs
(3ChdgG (B:s
(3hef fXe bUjOI aj GdeOjM GdfHhj, hgj JJVef GSeg hGdOYGA dg aj ChGFd MQha GdCHjGJ JbHd Gddg efg s
(3BNQgG (B:s
(3hCZaQ dfGXegG GdeJQLe HGSeg hOYGFg aj eHJOC ChRGfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3dYdg(B: (3eMeO Hf YHOGddg Hf MSf GdeGdbjs
(3CHhYHOGddg GdeJhai (B519(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs